FK506 inhibits the mice glomerular mesangial cells proliferation by affecting the transforming growth factor-β and Smads signal pathways. (May 2014) - Qi, Ren; Li, Wen; Yu, Shengyou
Abstract TGF-β1 plays an important role in the pathogenesis of chronic renal diseases. Although the specific mechanism is unknown, a major factor is the potent fibrogenic activity of TGF-β1 in the chronic progression of renal diseases. TGF-β1 closely correlates with renal fibrosis in cooperation with several fibrosis-promoting molecules. Recently it has been studied that, Smad proteins as intracellular mediators of TGF-β signaling pathways provide important insights into the mechanisms determining the specificity of TGF-β action in various renal cells. Some studies have proved that immunosuppressants can affect TGF-β expression, but the mechanisms are unclear. In this study, we investigated the effect of FK506 on mesangial cells via TGF-β and Smads signal pathways. Our results shows that FK506 effectively blocked the TGF-β/Smad signaling pathway by downregulation of TGF-β receptor, and played an important role in TGF-β1-induced Smad2 expression in mice mesangial cells. FK506 can inhibit the TGF-β1-stimulated cell proliferation via Smad-related pathways. And reduced the Smad2 protein and mRNA expression. Altogether, this study provided a theoretical proof for the protective and treating effect of FK506 on kidneys.